MONOCEPHALIC THORACOPAGUS CONJOINED TWIN IN A EWE - KUMARESAN, P; KUMAR, R ANIL; NAPOLEAN, R E; MANOHARAN, S; KARTHICK, C; SELVARAJU, M; PRABAHARAN, V; PALANISAMY, M (The Indian Journal of Animal Reproduction, 2023)
A case of monocephalic thoracopagus conjoined twin lamb in a Mecheri ewe was reported.